Self-Quenching Streamers in Mixtures with Photoionization Vapours - Lima, E. P. de (1983)
The basic properties of self-quenching streamers in a proportional counter with a thick anode wire are investigated. In particular, the influence of mixing benzene and triethylamine to argon-isobutane mixtures is studied regarding thresholds for streamer production, pulse shapes and dead time. There is a lowering of the high voltage threshold for streamer production associated with low concentrations of triethylamine and benzene. Higher concentrations of benzene increase that threshold. Triethylamine leads to narrower pulses. Stable operation is observed for a much broader range of high voltages than in the absence of photoionization vapours